Y=x2-2x+5

Simple and best practice solution for Y=x2-2x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y=x2-2x+5 equation:



=Y2-2Y+5
We move all terms to the left:
-(Y2-2Y+5)=0
We add all the numbers together, and all the variables
-(+Y^2-2Y+5)=0
We get rid of parentheses
-Y^2+2Y-5=0
We add all the numbers together, and all the variables
-1Y^2+2Y-5=0
a = -1; b = 2; c = -5;
Δ = b2-4ac
Δ = 22-4·(-1)·(-5)
Δ = -16
Delta is less than zero, so there is no solution for the equation

See similar equations:

| 144-4x=112 | | 2s+1=1 | | 16/x=176/165 | | 2s1=1 | | x=74-(2x+7) | | 6x+5/2=39 | | r/12=0 | | t=45+(45/2)+(0.2*45) | | |2x+5|=23 | | t=(45/2)+(0.2*45) | | 2p−5=3 | | t=(45/0.2)+(0.2*45) | | 5x+14=4x+16 | | 13x+2=5x+24 | | 3w+27=6w | | 18w-63=9w | | c=15(2)=29.50 | | -1/10(7x+5/2)=1/416/5x-25 | | 9x-4+4x=152 | | 7n-(2n+6)=17 | | 14t-77=3t | | 11(x-4)=10(x+4) | | 14t–77=3t | | x-5=0.5x-1 | | 3x2−x+2=(x−2)2 | | x-5=0.5x11 | | 3/2=5d-1/2​ | | 3(2x+2)−10=4(3−2x)−2x | | 9y+26=80 | | 3v+52=6v+49 | | -12x+6+7x=39 | | 2.5/9.2=t/8.3 |

Equations solver categories